Processing and characterization of nanocomposite based on poly(butylene/triethylene succinate) copolymers and cellulose nanocrystals. (1st June 2017) - Fortunati, Elena; Gigli, Matteo; Luzi, Francesca; Dominici, Franco; Lotti, Nadia; Gazzano, Massimo; Cano, Amalia; Chiralt, Amparo; Munari, Andrea; Kenny, Josè Maria; Armentano, Ilaria; Torre, Luigi
Highlights: Random eco-friendly copolyesters were successfully synthesized. Nanocomposites based on cellulose nanocrystals (CNC) were developed by extrusion. CNC modulated polymer mechanical properties. Extruded films displayed a tunable range of degradation rate. Abstract: A new class of biodegradable materials developed by a combination of random eco-friendly copolyesters containing butylene succinate (BS) and triethylene succinate (TES) sequences with cellulose nanocrystals (CNC), is proposed and studied. Polymers and nanocomposite films were prepared by an optimized extrusion process to improve the processability and mechanical response for flexible film manufacturing. Poly(butylene succinate) (PBS) homopolymer and two random copolyesters containing different amounts of TES co-units, P(BS85TES15) and P(BS70TES30), were synthesized by melt polycondensation. The effect of TES and CNC presence and content on the microstructure, tensile properties, thermal characteristics and disintegration under composting conditions, as well as on the toughening mechanism of the blends was investigated. Material properties were modulated by varying the chemical composition. CNC were used as reinforcement additive and their effect is modulated by the interaction with the three polymeric matrices. The extruded films displayed tunable degradation rates, mechanical properties and wettability, and showed promising results for different industrial applications.